Penerapan Pembelajaran Menggunakan Media Animaker untuk Meningkatan Minat Belajar Siswa pada Mata Pelajaran Informatika di SMP Negeri 1 Kramatmulya - Agustin, Aulia Magfiro; Lutfi, Ahmad Fajri (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Teaching is more varied and not easy to make students feel bored by using learning media can increase the desired students' interest in learning. This research aims to increase interest in learning using Animaker learning media in Informatics subjects. This type of research is quantitative research using a pre-expression research design of one group pretest-posttest design. The subjects in this study are 26 students in grade VII C SMP Negeri 1 Kramatmulya. In data collection, the author used multiple-choice posttest preetes and questionnaire questions. The data was analyzed using the data normality test, validity test and Reality test, and t-test. The results of the analysis that have been carried out show that there is a significant difference in the increase in students' interest in learning, and it is evidenced by the average pretest questionnaire score of 60.23 while the average score of the posttest is 63.61. So that the difference between the pretest and the posttest is 3.38. The data obtained shows that the students' response to the results of the application of animaker learning media is very good or there is an improvement compared to before using animaker media.